2016
DOI: 10.1080/21640629.2016.1195550
|View full text |Cite
|
Sign up to set email alerts
|

Sport coaches’ experiences of athlete injury: the development and regulation of guilt

Abstract: Abstract:This study sought to examine coaches' stories of guilt in the specific context of athlete injury. Using narrative interviews with a diverse group of ten coaches, guilt was found to be a commonly experienced emotion that the participants also sought to regulate. The coaches' experiences of the embodiment and management of guilt is primarily, although not exclusively, interrogated using the mainstream psychological theorising of Kubany and Watson (2003). The article concludes by connecting the coaches' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…For example, analysis revealed that observing athletes get injured was a stressful experience for physiotherapists, which triggered feelings of guilt, anger, and frustration. This finding resonates with recent research in the sport psychology literature that has examined the concept of vicarious trauma with athletes and coaches (Day, Bond, & Smith, 2013; Martinelli, Day, & Lowry, 2017). Clearly, stress management interventions in sport should not only focus on athletes but also target members of the “team behind the team.”…”
Section: Discussionsupporting
confidence: 85%
“…For example, analysis revealed that observing athletes get injured was a stressful experience for physiotherapists, which triggered feelings of guilt, anger, and frustration. This finding resonates with recent research in the sport psychology literature that has examined the concept of vicarious trauma with athletes and coaches (Day, Bond, & Smith, 2013; Martinelli, Day, & Lowry, 2017). Clearly, stress management interventions in sport should not only focus on athletes but also target members of the “team behind the team.”…”
Section: Discussionsupporting
confidence: 85%
“…Guilt is an emotion that can be found in sports at different levels. It can be found among coaches who perceive themselves as guilty when an injury occurs to the athletes they train (Martinelli et al, 2017 ). It can also be observed among athletes who make mistakes and, consequently, feel guilty for causing problems to their teammates (Jones, 2003 ).…”
Section: Discussionmentioning
confidence: 99%